PERSEPSI PETANI PADI TERHADAP PERAN PENYULUH PERTANIAN DAN GAPOKTAN DI DESA BUKIT RAYA KECAMATAN TENGGARONG SEBERANG (Perception of Paddy Farmers on the Role of Agricultural Extension Worker and Gapoktan in Bukit Raya Village, Tenggarong Seberang Subregency) - NASRIANSYAH NASRIANSYAH; SYARIFAH MARYAM; SITI BALKIS (Universitas Mulawarman (University of Mulawarman), 2021)
Perception is a direct response of something. The process of a person knows things through his five senses. This study aimed to determine paddy farmers perceptions on the role of agricultural extension worker and Gapoktan in Bukit Raya Village, Tenggarong Seberang Subregency, Kutai Kartanegara Regency. This study collected primary data and secondary data. Sampling used purposive method and number of samples of 40 respondents. Data were analyzed by descriptive. The results of this study showed farmers perception on the role of field agriculture instructure has a total score of 3,551 and it is classified as good. While farmers perception on the role of Gapoktan has a total score of 1,706 and it is classified as good.